Fenomena living qur’an dalam kitab hizib rizqi: Rekonstruksi sejarah penggunaan surat al-waqi’ah sebagai wirid dan ijazah - Aunillah Reza Pratama (Al Irfani: Journal of Al Qur'anic and Tafsir, 2022)
The tendency of the performative aspect of the Qur'an appears to be dominant when the holy text is received in society. Interestingly, it is the works of the scholars who become the embryo as well as the stimulus for such a phenomenon, such as works on the properties of the Qur'an and so on. The book Hizib Rizqi is one of the books that displays the performative aspects of Surah Al-Waqi'ah by stating that with certain practices and procedures, Al-Waqi'ah will display its benefits in the form of economic smoothness. This study discusses the phenomenon of the living Koran in Hizib Rizqi's book and its historical dynamics. This qualitative research seeks to answer what are the factors that shape it and how are its historical dynamics so that its existence survives in the present. The results of this study are: first, Hizib Rizqi's book displays performative aspects of Al-Waqi'ah's letter in certain ways or reading practices. This book also tries to affirm that the economic aspects of Surah Al-Waqi'ah have strong legitimacy in the form of hadith texts and the traditions of previous scholars recorded in the books. Second, the tradition of wirid and diploma in the tarekat is a vessel for various forms of reciting Al-Waqi'ah. The tarekat also contributes to the continuity of this practice and raises the possibility of more varied reading practices in the future.